Pemberdayaan UMKM Olahan Belimbing Wuluh dan Stik Lele Sebagai Produk Desa Wisata di Keluarah Sambikeep, Kecamatan Sambikerep, Kota Surabaya - Novaninda Ayu Cipta; Niniek Imaningsih; Cholid Fadil (Faculty of Law, 2022)
Abstract Covid 19 pandemic which occurred since early 2020 turned out brought so many significant effect on every aspect of life including on economics aspect. There are restrictions on every activities. Because of that, there will be a decreasing of sale on business things including small and micro enterprises. There are so many actors on small and micro enterprises complained about the decreasing of sale on small and micro enterprises. So, online media highly needed on increasing the sale. Students of KKNT 83 UPNVJT has a goal do a branding on one of superior small and micro enterprises in Sambiarum which is small and micro enterprises made from processed bilimbi. Branding is one of the most important thing for actors in business. Branding helps actors of small and micro enterprises to promote their product more. Since it helps a lot to promote more, we have an urge to help branding of Sambiarum’s superior small and micro enterprises from belimbing wuluh and catfish stick. The activities we did is made poster design and do a photography product. Reasearch method which we do is with observation and interview. These activities aim to make a more fresh image from the product so that it will increase the sale and attract new customer Keywords: Branding; Packaging; UMKM; Product.